Dual-loop single dimension fuzzy-based sliding mode control design for robust tracking of an underactuated quadrotor craft - Abro, G.E.M. (John Wiley and Sons Inc, 2022)
This manuscript presents an intelligent control design for the helical trajectory tracking of an underactuated quadrotor. One may see that the entire kinematics and dynamics are derived using Newton Euler approach. Since the quadrotor is one of the nonlinear and underactuated systems (where degree of freedom is greater than the number of control inputs) and with the induction of unmodeled dynamic factors and uncertainties, it is a highly unstable system. To stabilize, the linear extended state observer is proposed along with dual-loop single dimension fuzzy-based sliding mode control (DLSDF-SMC). The entire system has been partitioned into two subsystems, that is, translational and rotational subsystems. Within the rotational subsystem, the attitude controller is proposed using DLSDF-SMC, whereas for translational subsystem, paper proposes the position control design based on the hyperbolic functions to avoid the gimbal lock and an issue of singularity. The simulation work for proposed algorithm is performed using MATLAB and Simulink that are compared with conventional sliding mode control (SMC) and fuzzy-based SMC control techniques. In addition to this, one may also find the hardware configuration that validates the software results. Â© 2022 Chinese Automatic Control Society and John Wiley & Sons Australia, Ltd.